Evolution of Telepathology: A Comprehensive Analysis of Global Telepathology Literature Between 1986 and 2017 - Engin ŞENEL; Yılmaz BAŞ (Türk Patoloji Dergisi, 2020)

(untitled)
Objective: Telepathology is an application of telemedicine providing remote evaluation and consultation of digital pathology images and can be used for educational or experimental purposes. Bibliometrics is a statistical discipline investigating publication patterns and trends in a certain academic field. Although bibliometric and scientometric studies are becoming increasingly popular, the relevant literature contains only one limited article related to telepathology. The aim of our study was to perform a holistic bibliometric analysis of the telepathology literature.